Imperatorin’s Effect on Myocardial Infarction Based on Network Pharmacology and Molecular Docking - Ruizhe Zhang; Peng Wang; Yao Jin; Qingya Xie; Pingxi Xiao (Cardiovascular Therapeutics)
Conclusion: Imperatorin attenuated MI by inhibiting the ACE–Ang II–AT1R axis. Thus, imperatorin might be considered a potential therapeutic agent to cure MI.